Burkholderia gladioli MB39 an Antarctic Strain as a Biocontrol Agent - Sarli, Dinorah Anabella; Sanchez, Leandro Arturo; Delgado, Osvaldo Daniel (Current Microbiology)
Bioprospecting sub-explored environments such as Antarctic locations leads to finding out diverse activities, reducing harmful chemical usage that affects both human health and the environment. In this study, ~ 7000 cold-adapted bacterial strains were isolated from samples around Melchior Antarctic Base at 5 °C and more than 13,000 at 15 °C. Out of them, 900 different colony morphotypes were evaluated for antimicrobial production, and 13 isolates demonstrated antibacterial and antifungal activities. One isolate, closely related to Burkholderia gladioli according to 16S rDNA (99.8%), gyrB (99.6%) and Cpn60 (99.4%) gene sequence analysis, showed a consistent, broad antimicrobial spectrum against both pathogenic and phytopathogenic bacteria. Its potent antifungal activity inhibits the growth of various plant pathogenic fungi, whereas it was mainly studied against Penicillium digitatum and Macrophomina phaseolina, the causal agents of blue mould in postharvest fruits and charcoal rot in soybean crops, respectively. The antibacterial compound exhibited low molecular weight (< 6000 Da), resistance to lytic enzymes and stability in a broad range of temperature and pHs. Observations of the B. gladioli MB39 antifungal effects over M. phaseolina mycelia by scanning electron microscopy showed alterations in hyphal structures, reduced hyphal extension, and severe cell morphology changes such as cytoplasmic leakage, flattened and empty mycelia. Here we report the isolation and identification of a cold-adapted B. gladioli strain. The results describe the effectiveness of the antarctic strain for bacterial and fungal phytopathogens biocontrol and its potential for crop protection plans. Fil: Sarli, Dinorah Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Sanchez, Leandro Arturo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - ...